Kartu Kredit Dan Nasabah( Studi Tentang Hubungan Hukum Antara Bank Dan Pemegang Kartu Kredit Di Kantor Cabang Utama Bank Bca Surakarta ) - Putri, Kiki Yunitasari Saras; , Septarina Budiwati, S.H., M.H (2016)
Credit card allows customers to "suspend " their bills, but will add a penalty they must pay , the cardholder will carry out a transaction with a merchant , then the signing of a memorandum of transactions or sales slip , followed by the delivery of goods or services, after the trader or merchant will filed a claim money according to the memorandum of transactions or sales slip. Publisher or receiving bank credit card bill will transfer the money to the merchant at reduced commission to the beneficiary bank, eg 3%. After that the issuing bank will be charging a credit card to credit card holders in accordance with the memorandum of transactions or sales slip. Cardholders who receive these bills will make payments in accordance with the memorandum of transactions or sales slip. Publishers will issue a credit card bill on the appointed day in a month , the credit card holder must pay before the grace period ends, the rest, the late fee must be paid .